The Internet as a Source of Academic Research Information: Findings of Two Pilot Studies - Kibirige, Harry M.; DePalo, Lisa (Information technology and libraries, 2000)
As a source of serious subject-oriented information, the Internet has been a powerful feature in the information arena since its inception in the last quarter of the twentieth century. It was, however, initially restricted to government contractors or major research universities operating under the aegis of the Advanced Research Projects Network (ARPANET).(1) In the 1990s, the content and use of the Internet was expanded to includemundane subjects covered in business, industry, education,government, entertainment, and a host of otherareas. It has become a magnanimous network of networks the measurement of whose size, impact, and content often elude serious scholarly effort.(2) Opening the Internet to common usage literally opened the flood gates of what has come to be known as the information superhighway. Currently, there is virtually no subject that cannot be found on the Internet in one form or another.